ALS‐linked KIF5A ΔExon27 mutant causes neuronal toxicity through gain‐of‐function. (23rd June 2022) - Pant, Devesh C; Parameswaran, Janani; Rao, Lu; Loss, Isabel; Chilukuri, Ganesh; Parlato, Rosanna; Shi, Liang; Glass, Jonathan D; Bassell, Gary J; Koch, Philipp; Yilmaz, Rüstem; Weishaupt, Jochen H; et al.
Abstract: Mutations in the human kinesin family member 5A ( KIF5A ) gene were recently identified as a genetic cause of amyotrophic lateral sclerosis (ALS). Several KIF5A ALS variants cause exon 27 skipping and are predicted to produce motor proteins with an altered C‐terminal tail (referred to as ΔExon27). However, the underlying pathogenic mechanism is still unknown. Here, we confirm the expression of KIF5A mutant proteins in patient iPSC‐derived motor neurons. We perform a comprehensive analysis of ΔExon27 at the single‐molecule, cellular, and organism levels. Our results show that ΔExon27 is prone to form cytoplasmic aggregates and is neurotoxic. The mutation relieves motor autoinhibition and increases motor self‐association, leading to drastically enhanced processivity on microtubules. Finally, ectopic expression of ΔExon27 in Drosophila melanogaster causes wing defects, motor impairment, paralysis, and premature death. Our results suggest gain‐of‐function as an underlying disease mechanism in KIF5A‐associated ALS. Synopsis: The ALS‐associated KIF5A ΔExon27 mutation drives the disease via a gain‐of‐function mechanism caused by constitutive activation and increased motor association and aggregation of mutant KIF5A. KIF5A ΔExon27 is aggregation‐prone and is neurotoxic. KIF5A ΔExon27 displays relieved autoinhibition, increased motor self‐association, and enhanced processivity on microtubules. ALS patient iPSC‐derived motor neurons express mutant KIF5A proteins. Ectopic expression of KIF5A ΔExon27 in Drosophila leads to abnormal wings, motor deficits, paralysis, and premature death. Abstract : The ALS‐associated KIF5A ΔExon27 mutation drives the disease via a gain‐of‐function mechanism caused by constitutive activation and increased motor association and aggregation of mutant KIF5A.